Explorando el efecto de las redes sociales en Entornos Personales de Aprendizaje en el ámbito universitario: análisis de experiencias y detección de futuros desafíos - Gil-Fernández, Raquel; Calderón-Garrido, Diego; Martín-Piñol, Carolina (RED. Revista de Educación a Distancia, 2024)
The concept of PLEs as connected learning and the shaping of them as a socio-material framework in which people learn, overlaps with the intrinsic characteristics of social media. Consequently, it is important to analyse how academic literature has treated the direct relationship between the two realities in the university sector. Accordingly, the objective of this work is to determine how this relationship has been treated with regards to contexts, authorship and positions, types of social media, objectives pursued, methodologies and results. Regarding methodology, we used the PICOC strategy to design the research questions and the PRISMA protocol to document the systematic review of academic production in SCOPUS and Web of Science between 2012 and 2021. We ultimately obtained a sample of 35 works. The findings show that use of media to build PLEs that meet users’ needs should be explored in greater depth and analysed by using particular methodologies to reach conclusions that help to drive them. Academic and professional promotion stand out among the major challenges in the use of social media in PLEs, as does the possibility of bringing together non-formal, formal, and informal areas to create learning.
Exploring the effect of social media in Personal Learning Environments in the university settings: analysing experiences and detecting future challenges
Keywords: entornos personales de aprenzaje; redes sociales; aprendizaje autorregulado; aprendizaje en red; revisión sistemática; personal learning environments; social media; self-regulated learning; online learning; systematic review; Emerging